2022
DOI: 10.1175/jhm-d-21-0229.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Snow Water Equivalent on Streamflow Predictability during Drought

Abstract: Snowpack provides the majority of predictive information for water supply forecasts (WSFs) in snow-dominated basins across the western US. Drought conditions typically accompany decreased snowpack and lowered runoff efficiency, negatively impacting WSFs. Here, we investigate the relationship between snow water equivalent (SWE) and April-July streamflow volume (AMJJ-V) during drought in small headwater catchments, using observations from 31 USGS streamflow gages and 54 SNOTEL stations. A linear regression appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Furthermore, the SCS curve number of the HEC HMS Model was applied to verify the peak discharge. This study analyzed the relationship between temperature and snow water equivalent (SWE) of the Melamchi catchment using regional equation (DHM, 2006) and then SWE was converted in to stream ow (Modi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the SCS curve number of the HEC HMS Model was applied to verify the peak discharge. This study analyzed the relationship between temperature and snow water equivalent (SWE) of the Melamchi catchment using regional equation (DHM, 2006) and then SWE was converted in to stream ow (Modi et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the Himalaya, snowmelt also has signi cant contribution to total runoff of the river (Li et al 2017;ICIMOD, 2011). During summer, snowmelt water i.e amount of snow water equivalent (SWE) has positively correlated with stream ow in the rivers of Himalayas (Modi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the lack of or limited snow accumulation in winters plays an important role in the following period of streamflow (Dierauer et al, 2018) and its predictability during drought periods (Modi et al, 2022), and groundwater recharge and its monitoring (Sit et al, 2021). Understanding snow accumulation is an important factor for flood forecasting (Krajewski et al, 2021;Muste et al, 2022) and mapping to support mitigation (Alabbad et al, 2022) and agricultural planning decisions (Yildirim and Demir, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In mountainous, snow‐dominant watersheds, these estimates are needed for streamflow forecast modeling and reservoir management. Knowledge of initial hydrologic conditions (i.e., snow depth at the beginning of the melt season) drives forecasting skill (Anghileri et al., 2016), so timely and spatially distributed observations of snowpack state are needed for accurate forecasting and management, especially during anomalous years (Modi et al., 2022) and in a changing climate (e.g., Gordon et al., 2022; Marshall et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In mountainous, snow-dominant watersheds, these estimates are needed for streamflow forecast modeling and reservoir management. Knowledge of initial hydrologic conditions (i.e., snow depth at the beginning of the melt season) drives forecasting skill (Anghileri et al, 2016), so timely and spatially distributed observations of snowpack state are needed for accurate forecasting and management, especially during anomalous years (Modi et al, 2022) and in a changing climate (e.g., Gordon et al, 2022;Marshall et al, 2019).Stereo photogrammetry with very-high-resolution (VHR, <1-2 m resolution) optical satellite images provides digital elevation models (DEMs) that can precisely measure snow surface elevation. These "snow-on" DEMs offer fine-scale snow depth mapping when differenced with a snow-free DEM.…”
mentioning
confidence: 99%